Similar Interstage Outcomes for Single Ventricle Infants Palliated With an Aortopulmonary Shunt Compared to the Norwood Procedure. Issue 4 (July 2018) - Pizzuto, Matthew; Patel, Mehul; Romano, Jennifer; Retzloff, Lauren; Yu, Sunkyung; Lowery, Ray; Gelehrter, Sarah
Background: Interstage outcomes for single ventricle infants following Norwood operation have been well studied, showing significant mortality. Other single ventricle infants require only an aortopulmonary shunt. The aim of the study was to describe the interstage outcomes of this group compared to Norwood patients and identify risk factors for mortality. Methods: A single-center retrospective cohort review was performed in patients who underwent a Norwood operation (Norwood) or aortopulmonary shunt (Shunt) during 2000 to 2011 and survived to discharge. Hybrid or pulmonary artery banding patients were excluded. Univariate comparison was made between Norwood and Shunt patients as well as a Shunt subgroup analysis. Results: A total of 486 patients (368 Norwood and 118 Shunt) were included. Norwood and Shunt patients were similar in terms of preterm birth, surgery weight, and stage 1 complications. Shunt patients were more likely to be female, have an extracardiac or genetic anomaly, and have a shorter hospital length of stay compared to the Norwood patients (all P < .0001). No significant difference in interstage mortality was seen between the Shunt and Norwood patients (6.8% vs 11.1%, respectively; P = .17). Stage 2 mortality was also similar (Shunt 4.6% vs Norwood 7.8%; P = .25). In the Shunt patients, those who died during interstage weighed less at surgery (2.7 [0.7] kg vs 3.3 [0.7] kg, P = .03) and were more likely to have arrhythmias (50% vs 12%, P = .01), compared to survivors. Conclusions: Shunt patients have an interstage mortality that is not significantly less than Norwood patients. Lower weight at surgery and arrhythmias are risk factors for interstage death in Shunt patients.